Linguistic situation of the south-east region and taking into consideration it’s influence on to the process of education of preschool children of the Ukrainian language (Pedagogy of Higher and Secondary Education, 2013)
Kazantseva L. I. Linguistic situation of the south-east region and taking into consideration it’s influence on to the process of education of preschool children of the Ukrainian language.Peculiarities of the linguistic situation of the south-east region of Ukraine are determined, the characteristics of the sociolinguistic environment as a factor of the formation of a preschool child’s  personality are given.
Keywords: linguistic situation; sociolinguistic environment; bilingualism; vernacular; dominant language; Ukrainian-speaking; Russian-speaking